2016
DOI: 10.1038/pr.2016.118
|View full text |Cite
|
Sign up to set email alerts
|

Early docosahexaenoic and arachidonic acid supplementation in extremely-low-birth-weight infants

Abstract: Background: Extremely-low-birth-weight (ELBW) infants accrue large deficits in docosahexaenoic acid (DHA) and arachidonic acid (ARA) and require improved supplementation strategies. We hypothesized that once daily DHA+ARA drops applied to buccal mucosa will increase blood levels. Methods: Thirty ELBW infants were randomized to receive DHA 20 mg/kg/d + ARA 40 or 60 mg/kg/d + ARA 120 mg/kg/d or placebo within 72 h of age for 8 wk duration. Red blood cell phospholipid levels of DHA (primary) and ARA (secondary) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…While DHA supplementation did significantly increase DHA levels in infants, the DHA levels at discharge in supplemented preterm infants remained significantly lower than term infant values [ 33 ]. Another recent study looking at delivering DHA via the buccal method found that this method did not alter DHA levels after 8 weeks of supplementation [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…While DHA supplementation did significantly increase DHA levels in infants, the DHA levels at discharge in supplemented preterm infants remained significantly lower than term infant values [ 33 ]. Another recent study looking at delivering DHA via the buccal method found that this method did not alter DHA levels after 8 weeks of supplementation [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Afterward, Collins et al administered DHA as an emulsion (at doses 40, 80, and 120 mg/kg), finding that higher DHA supplementation was directly related to blood DHA levels ( 23 ). Previous studies using nonemulsified fatty acids have not been able to show differences in fatty acid levels ( 37 ). Although our emulsion has a small particle size (90% of the particles were smaller than 1.89 μm), in vitro digestion tests have shown limited digestibility that limits bioavailability, which may explain why higher differences were not found between the two groups.…”
Section: Discussionmentioning
confidence: 93%
“…For example, the DHA status of extremely low birth weight (ELBW) infants declines significantly in the first 2 months after birth, particularly in infants exposed to IVLEs for more than 28 days [ 13 ]. This low DHA status can remain for weeks, even after the establishment of full enteral feeding [ 14 ]. Several other plasma fatty acids abnormalities such as low (AA) and high linoleic acid (LA) are also described in very preterm infants [ 15 ].…”
Section: Postnatal Fatty Acid Status In Preterm Infantsmentioning
confidence: 99%
“…Monounsaturated fatty acids (MUFAs) have one double bond, whereas polyunsaturated fatty acids (PUFAs) have several. LC-PUFAs (18 or more carbons) comprise 90% of all PUFAs in breastmilk [ 14 ]. They are classified into two key families: n3 and n6, depending on the position of the first double bond in the hydrocarbon chain.…”
Section: Fatty Acids Of Breastmilkmentioning
confidence: 99%